PROSPECTS FOR IMPROVING THE PENSION SYSTEM IN UZBEKISTAN - Achilov Uygunjon Ulugbekovich (Western European Studies, 2024)
This scientific article is devoted to study of the public pension provision system in Uzbekistan. The article studies the stages of evolution of the national pension system, the current state and development trends of pension provision, and identifies problems in the pension system of Uzbekistan. Basing on the research results the authors have developed scientific proposals and practical recommendations.
Keywords: pension; pension provision; old-age pension